2014
DOI: 10.1007/s12012-014-9266-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinases Pathways Mediate the Sunitinib-Induced Hypertrophy in Rat Cardiomyocyte H9c2 Cells

Abstract: Sunitinib (SUN) is a multi-targeted tyrosine kinase inhibitor used for the treatment of gastrointestinal stromal tumors and renal cell carcinoma. Cardiotoxicity has been reported as a significant side effect associated with the SUN treatment, yet the mechanism is poorly understood. The main purpose of this study was to investigate the potential effects of SUN on cardiac hypertrophic genes and the role of mitogen-activated protein kinases (MAPKs) signaling pathway in rat cardiomyocyte H9c2 cell line. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 50 publications
3
14
0
Order By: Relevance
“…After confirming the effects of AOF treatment on pathological hypertrophy associated signaling pathways, we investigated the physiological hypertrophy-related markers BNP, MYH6, and MYH7 [5254] protein levels by Western blot analysis. Our results showed that D-galactose-induced aging effects caused a significant increase in the protein expression levels of both BNP and MYH7 by approximately twofold and 40%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…After confirming the effects of AOF treatment on pathological hypertrophy associated signaling pathways, we investigated the physiological hypertrophy-related markers BNP, MYH6, and MYH7 [5254] protein levels by Western blot analysis. Our results showed that D-galactose-induced aging effects caused a significant increase in the protein expression levels of both BNP and MYH7 by approximately twofold and 40%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We further investigated the potential mechanism of HG-induced BRD7 expression in vitro. ERK1/2 is strongly activated by HG stimulation [35]. A recent study showed that activation of Ras/Raf/MEK/ERK pathway increased BRD7 expression in hepatoma cell during HCV infection [36].…”
Section: Discussionmentioning
confidence: 99%
“…The major MAPK signaling cascades ERK1/2, p38, and JNK are strongly activated by HG [ 46 ]. They participated in the progression of cellular hypertrophy, apoptosis, cardiac fibrosis, and cardiac cytokine-mediated inflammation, which were involved in the development of DCM [ 47 ].…”
Section: Discussionmentioning
confidence: 99%